2014
DOI: 10.1586/14760584.2014.942641
|View full text |Cite
|
Sign up to set email alerts
|

Genetically detoxified pertussis toxin (PT-9K/129G): implications for immunization and vaccines

Abstract: Pertussis toxin (PT) is one of the major virulence factors of Bordetella pertussis and the primary component of all pertussis vaccines available to date. Because of its various noxious effects the toxin needs to be detoxified. In all currently available vaccines, detoxification is achieved by treatment with high quantity of chemical agents such as formaldehyde, glutaraldehyde or hydrogen peroxide. Although effective in detoxification, this chemical treatment alters dramatically the immunological properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 88 publications
2
33
0
1
Order By: Relevance
“…It is thus urgent to define whether improved booster vaccines might be developed for future aP-primed pregnant women. Existing options include the use of genetically detoxified PT, shown to be more immunogenic than chemically detoxified PT, inducing higher neutralizing antibody titers and a Th1/ Th17 response that may improve mucosal responses (Seubert et al 2014). To reduce immune escape, additional antigens such as improved fimbriae antigens (Gorringe and Vaughan 2014), adenylate cyclase toxin (ACT), or the autotransporter BrkA could be considered (Brummelman et al 2015).…”
Section: What Lies Ahead?mentioning
confidence: 99%
“…It is thus urgent to define whether improved booster vaccines might be developed for future aP-primed pregnant women. Existing options include the use of genetically detoxified PT, shown to be more immunogenic than chemically detoxified PT, inducing higher neutralizing antibody titers and a Th1/ Th17 response that may improve mucosal responses (Seubert et al 2014). To reduce immune escape, additional antigens such as improved fimbriae antigens (Gorringe and Vaughan 2014), adenylate cyclase toxin (ACT), or the autotransporter BrkA could be considered (Brummelman et al 2015).…”
Section: What Lies Ahead?mentioning
confidence: 99%
“…Both goals will require reformulation of pertussis vaccine constituents, both antigens and adjuvants. The most obvious strategies are to use genetically rather than chemically inactivated PT (Seubert et al 2014); to use adjuvants that better stimulate innate immunity and memory; and/or to add new B. pertussis virulence factors to the vac- Figure 2. New aP vaccine should be aimed to increase priming and boostability of current subunit vaccine through the addition of adjuvants that will program a more Th1/Th17 immune profile and possibly the addition of more subunit Ags inducing bactericidal activity to limit or prevent colonization.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the use of rPT improves protective efficacy against wild-type strains [6]. A recent clinical study indicated that boosting with rPT was safe and induced significantly higher neutralizing antibodies than current acellular pertussis vaccines (BioNet forthcoming data, http://www.businesswire.com/ news/home/20141015006848/en/BioNet-Update-RecombinantAcellular-Pertussis-Vaccine-BioJapan#.VGK69skVji0).…”
Section: Discussionmentioning
confidence: 99%
“…Novel strategies would thus be welcome. The use of poorly immunogenic chemically-detoxified pertussis toxin (PT) likely contributes to limit pertussis immunity [5]: it removes up to 80% of surface epitopes, reducing neutralizing antibodies, and directing B cells toward vaccine-specific rather than pathogen-specific epitopes [6]. PT with wild-type immunogenicity profile but deprived of toxicity is best achieved through genetic rather than chemical detoxification [6][7][8].…”
Section: Introductionmentioning
confidence: 99%